Effects of Morning’s Prayer Routines in The Congregation on Random Blood Sugar Levels of Elderly at Al Wahyu Mosque Rungkut Surabaya - Indri Ngesti Rahayu; Lani Diana; R. Varidianto Yudo Tjahjono (Denta Journal Kedokteran Gigi, 2021)
Background: Increased health problems in the elderly occur because of the aging process that causes many changes in their body. One of the changes istheincrease in blood glucose more than normal and at risk of diabetes mellitus. Morning prayer can be a religious coping and regular physical activity that lowers blood sugar levels. Objective: to analyze the effect of the morning prayer routines in the congregation on random blood sugar levels of the elderly at Al-Wahyu Mosque Rungkut Surabaya. Method:This study was an observational analytic study with a cross-sectional design using 30 respondents. The group studied was the congregation of the morning prayers of the Al Wahyu MosqueRungkut Surabaya which was over 45-year-old which undergoes random blood sugar levels measurement. Results:The Independent t-testmethodshowedthat the value of signification was 0,000 (p<0,05) which means that there is the influence of the morning prayer’s routines in the congregation on random blood sugar levels of the elderly at Al-Wahyu Mosque Rungkut Surabaya. Conclusion:Elderly people who routinely carry out the morning prayer routines in the congregation have lower blood sugar levels than elderly people who are not routine.